O espaço existencial em xeque: uma odisseia para o espaço ontológico na Geografia - GUIMARÃES, Humberto Goulart (UFPR, 2010)
The academic Geography has as basis the aristotelian-kantian impasse and the baconian-cartesian-newtonian paradigm. These problems emerge a logical complication, referring the space an epistemological approach, of external characteristic to human existence. The fruits are the dichotomies: man/nature, man/environnement and man/space. The author searches to express some critical conceptions intercross Geography and Philosophy for the change of existential space, putting it in check.